DNA gains and losses in gigantic genomes do not track differences in transposable element-host silencing interactions - Jie Wang; Guangpu Zhang; Cheng Sun; Liming Chang; Yingyong Wang; Xin Yang; Guiying Chen; Michael W. Itgen; Ava Haley; Jiaxing Tang; Rachel Lockridge Mueller (Communications Biology)
Abstract Size evolution among gigantic genomes involves gain and loss of many gigabases of transposable elements (TEs), sequences that parasitize host genomes. Vertebrates suppress TEs using piRNA and KRAB-ZFP pathways. TEs and hosts coevolve in an arms race, where suppression strength reflects TE fitness costs. In enormous genomes, additional TE costs become miniscule. How, then, do TEs and host suppression invoke further addition of massive DNA amounts? We analyze TE proliferation histories, deletion rates, and community diversities in six salamander genomes (21.3 - 49.9 Gb), alongside gonadal expression of TEs and suppression pathways. We show that TE activity is higher in testes than ovaries, attributable to lower KRAB-ZFP suppression. Unexpectedly, genome size and expansion are uncorrelated with TE deletion rate, proliferation history, expression, and host suppression. Also, TE community diversity increases with genome size, contrasting theoretical predictions. We infer that TE-host antagonism in gigantic genomes produces stochastic TE accumulation, reflecting noisy intermolecular interactions in huge genomes and cells.